PENGARUH KREDIT BERMASALAH, PORSI KREDIT, TINGKAT EFISIENSI, DAN KEMAMPUAN MODALTERHADAP PROFIRABILITAS PADA BANK PERKREDITAN RAKYAT DI SUMATERA BARAT PERIODE 2013-2016 - Istiqomah Azizah, 14.05.52.0043; N. Masdjojo, Gregorius (Students Journal of Accounting and Banking, 2018)
This study aims to analyze the effect of Non Performing Credit, Credit Portion, Efficient Level and Capital Capacity to Profitability. The population in this study are all BPRs in West Sumatra registered in the Financial Services Authority of 2013-2016.Sampling method using purposive sampling with criteria, BPR data used is secondary data taken from the OJK Publications Report, and publish the financial statementsconsistently. Due to the combined data type between cross-section and time series, the analysis method used is panel data regression analysis with Fixed Effect (FEM) and Random Effect (REM) estimation. Model selection using Hausman Test.The Hausman Test results recommend the research using Fixed Effect estimation output For hypothesis testing analysis. The result of the research shows that Problem Credit, Efficiency Level and Capital Ability have negative and significant effect to Profitability. While Credit Portion has positive and insignificant effect. The value of Adjusted R2 of 0.4017 indicates that 40.17% of the dependent variable Profitability can be explained by the independent variable of Problem Credit, Credit Portion, Efficiency Level and Capital Capability. The remaining 59.8% is explained by other factors not included in this regression model